Peranan Konseling Individual dalam Pemulihan Korban Pasca Banjir - Ainul Mardiyah; Tegar Arbia Sukma; Muhammad Yusuf Kamala; Ilmi Shobron (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
The flood disaster that hit Medan City caused a multidimensional impact on the community, especially the psychological impact experienced by the victims. In addition to material losses, flood victims often face emotional distress in the form of anxiety, stress, trauma, and a sense of loss. This study aims to examine the role and effectiveness of individual counseling in dealing with the psychological problems of post-flood victims. The research method uses a qualitative approach with case studies through in-depth interviews, observations, and documentation of victims who receive individual counseling services. The results show that individual counseling plays an important role in helping victims understand their emotional state, manage stress, and rebuild hope and resilience after disasters. Individualized counseling also provides a safe space for victims to express their feelings, gain support, and develop adaptive strategies in dealing with trauma. These findings confirm that psychological interventions based on individual counseling can be one of the effective approaches in disaster victim recovery, especially floods, so that it can strengthen psychosocial aspects and improve the quality of life after disasters. Thus, this research contributes to the development of more responsive and sustainable counseling services in the context of disaster management in Indonesia.